Indirect laminate veneer: a conservative novel approach. (23rd August 2013) - Prajapati, Paranjay; Sethuraman, Rajesh; Naveen, Y G; Patel, Jayanti R
Abstract : Various treatment options and materials are available for restoration of an endodontically treated tooth. Laminate veneer is conservative treatment usually employed for aesthetic correction or improvement. The indirect composite is available in a wide range of shades and specific characterisation is easily performed chair side in the operatory area, which makes it a quick procedure and time saving for both the patient and the dentist. The physical properties and optical properties are good enough to use it as indirect restorative material, so in this particular case it was the material of choice for fabrication of laminate veneer on anterior tooth. In this case, the endodontically treated tooth with a fractured incisal edge was restored with indirect composite material.